2004
DOI: 10.1185/030079904x2754
|View full text |Cite
|
Sign up to set email alerts
|

Topical lidocaine patch 5% may target a novel underlying pain mechanism in osteoarthritis

Abstract: Recent literature and animal research has provided insight to potentially new analgesic targets for managing osteoarthritis (OA) pain. Primary afferent neurons located in affected joints express excessive amounts of abnormally functioning sodium (Na) channels on their surface in response to the inflammatory process. These Na channels may play an integral role in production of pain and hyperalgesia. Hence, the authors set out to conduct a 2-week, open-label, multicenter proof-of-concept study to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 7 publications
3
25
0
10
Order By: Relevance
“…6,15,18,21,23,24,44 Analyses of changes with lidocaine patch 5% treatment in several of these studies for NPS items and scales and of the relationships between NPS items and physical and emotional functioning have been reported previously. 2,19,22,26,27 All participants provided informed consent before any study procedures were initiated.…”
Section: Study Participants and Proceduresmentioning
confidence: 96%
“…6,15,18,21,23,24,44 Analyses of changes with lidocaine patch 5% treatment in several of these studies for NPS items and scales and of the relationships between NPS items and physical and emotional functioning have been reported previously. 2,19,22,26,27 All participants provided informed consent before any study procedures were initiated.…”
Section: Study Participants and Proceduresmentioning
confidence: 96%
“…The data for this study were obtained from 6 open-label trials of the analgesic. 1,5,[10][11][12]21 Except for some very minor variations, the procedures used in these studies were identical. Variations across the studies included (1) minor differences in the lengths of the trials, with post-treatment data available at 2 weeks for 4 of the studies and at 3 weeks for 2 studies and (2) slight differences in inclusion criteria (detailed below in the Methods section) as a result of differences in diagnoses.…”
mentioning
confidence: 99%
“…2,3,[9][10][11]14,15,30 Analyses of changes with 5% lidocaine patch treatment in several of these studies in ratings of pain qualities and locations have been previously reported, 1,10,11,13,18 as have analyses concerning the differences between diagnostic groups in response to the pain descriptor ratings. (Dworkin RH, Jensen MP, Gammaitoni AR, Olaleye DO, Oleka N, Galer BS, Symptom profiles differ in patients with neuropathic vs. non-neuropathic pain.…”
Section: Participantsmentioning
confidence: 99%